Root exudates facilitate the regulation of soil microbial community function in the genus Haloxylon - Wu, Deyan; He, Xuemin; Jiang, Lamei; Li, Wenjing; Wang, Hengfang; Lv, Guanghui (Frontiers in Plant Science, 2024)
Root exudates act as the "language" of plant-soil communication, facilitating crucial interactions, information exchange, and energy transfer between plants and soil. The interactions facilitated by root exudates between plants and microorganisms in the rhizosphere are crucial for nutrient uptake and stress resilience in plants.However, the mechanism underlying the interaction between root exudates and rhizosphere microorganisms in desert plants under drought conditions remains unclear, especially among closely related species. Therefore, this study aims to reveal the ecological strategies employed by the genus Haloxylon in different habitats. Here, we analyzed root exudates and soil microorganisms from two closely related species, Haloxylon ammodendron (HA) and Haloxylon persicum (HP), to assess differences in their root exudates, soil microbial composition, and interactions. Significant differences were found in soil properties and root traits between the two species, among which soil water content (SWC) and soil organic carbon (SOC) in rhizosphere and bulk soils (P < 0.05). While the metabolite classification of root exudates was similar, their components varied, with terpenoids being the main differential metabolites. Soil microbial structure and diversity also exhibited significant differences, with distinct key species in the network and differential functional processes mainly related to nitrogen and carbon cycles. Strong correlations were observed between root exudate-mediated root traits, soil microorganisms, and soil properties, although the complex interactions differed between the two closely relative species. The primary metabolites found in the network of HA include sugars and fatty acids, while HP relies on secondary metabolites, steroids and terpenoids. These findings suggest that root exudates are key in shaping rhizosphere microbial communities, increasing microbial functionality, fostering symbiotic relationships with hosts, and bolstering the resilience of plants to environmental stress.